Relationship between physical metrics and game success with elite rugby sevens players - Blair, M. R.; Body, S. F.; Croft, H. G. (International Journal of Performance Analysis in Sport, 2017)
The purpose of this study was to use self-organising maps (SOMs) to visualise the multivariate relationship between physical metrics (PM`s) as measured by GPS and how they relate to a performance outcome in elite-level 7s rugby. The players heart rate was elevated in the high intensity zone for an average of 73% per game and covered an average distance of 1574 m. Over this distance, 22% of the time was spent high-speed running and a relative distance of 112 m/min was travelled. SOMs showed no reliable relationship between PMs and points difference while two groups of PMs demonstrated similar patterns. This included variables such as high-speed running and metabolic power in the first group and all of the body composition variables in the second group. The final group of variables, including RPE had no relationship with any of the other PM variables. High-speed running and metabolic power are related closely and provide information that can be used for the preparation of 7s specific training schedules. RPE was shown to be unreliable as it did not relate well to any of the PMs.